Emulsion pce copolymers and their use as water reducing agents
Patent Information
- Application Number
- CN202580020194.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-03-13
- Filing Date
- 2025-03-27
- Publication Date
- 2026-10-09
AI Technical Summary
酯化反应具有高操作成本
[0039]本发明的PCE共聚物可以通过普通乳液聚合简单且廉价地以一致的特性制备。乳液聚合可以使用高载量的单体并且产生含有高载量PCE共聚物的水性分散体。该水性分散体可以有效地用于将PCE共聚物作为减水剂递送到水泥质混合物中,或者可以有效地喷雾干燥以制成粉末。与通过常规方法制备的PCE共聚物相比,一些PCE共聚物可以表现出优异的坍落度性能。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the fields of concrete, mortar, plaster and stucco. Background Technology
[0002] Mortar, plaster, stucco, and sometimes concrete (called cementitious mixtures) are typically prepared in two stages. First, a dry mixture containing cement, filler, and solid particulate additives (“dry components”) is blended together. Second, water is added to the dry mixture to create a wet mixture, which can be further formulated into the final cementitious mixture. The dry mixture is stable as long as it remains sufficiently dry; it can be stored for a long time and is easy to transport. The wet mixture begins to harden after the addition of water and must be used before it becomes difficult to work. (In the case of concrete, sometimes aggregate filler is mixed with water first, and then other components are added to create a wet mixture.)
[0003] The main components of the dry mixture are fillers and cement. The dry mixture components may also include small amounts of other additives, such as water-reducing agents, organic binders, cellulose ethers, starch ethers, fibers, air-entraining agents, curing accelerators, curing retarders, defoamers, and pigments.
[0004] The amount of water added to prepare the wet mixture is selected to provide a workable viscosity. The viscosity of mortar, plaster, and stucco wet mixtures should allow them to spread smoothly on a substrate without dripping and allow the cementitious mixture to adhere and bond to tiles or other materials pressed onto them. The viscosity of concrete should allow it to fill molds and formwork and, if necessary, be leveled to a smooth surface. The viscosity of a wet mixture is measured by slump—the extent to which the cone of the wet mixture expands after the supports are removed.
[0005] Water-reducing agents (also known as plasticizers, superplasticizers, or slump enhancers) allow cementitious mixtures to maintain a workable viscosity with less water. They are used to reduce the proportion of water in wet mixtures because wet mixtures containing less water are denser and form stronger cured concrete or mortar. The amount of water is measured by the density of the wet mixture; higher density indicates less water. Common types of water-reducing agents include lignin sulfonates, naphthalene sulfonate formaldehyde polymers, and polycarboxylate ether copolymers.
[0006] Polycarboxylate ether copolymers (PCE copolymers) offer excellent water-cement ratios in cementitious mixtures, along with good processability, reduced segregation, and improved surface finish. PCE copolymers comprise a backbone polymer chain of polycarboxylic acid (an acidic polymer). Multiple overhanging polyethylene glycol (PEG) polymer or oligomer chains are bonded to the backbone polymer via ester bonds. This structure is often referred to as a "comb" structure and is illustrated by the acidic polymer (like the spine of a comb) and the overhanging PEG chains attached to the backbone (like the teeth of a comb).
[0007] The methods for preparing PCE copolymers are inefficient and expensive.
[0008] Some PCE copolymers are prepared by solution copolymerization in an aqueous medium of unsaturated polyethylene glycol-containing monomers (such as polyethylene glycol methacrylate or PEGMA) and unsaturated carboxylic acid-containing monomers (such as methacrylic acid). Some of these monomers have low solubility in the aqueous polymerization medium, thus resulting in only low solids content. Furthermore, solution polymerization typically leads to a high-viscosity reaction mixture, which becomes difficult to maintain stirring or further process once the mixture cools. Excess water, glycol, or solvent can be added to reduce viscosity, but highly diluted solutions are inefficient for moving, storing, or recovering PCE copolymers.
[0009] Some PCE copolymers are prepared by grafting hydroxyl-terminated polyethylene glycol polymers onto acidic polymers using an esterification reaction. Esterification is a costly process. Furthermore, esterification rarely consumes all of the polyethylene glycol, leaving residual polyethylene glycol that is difficult to separate from the PCE product.
[0010] There is a desire to provide a more efficient method for preparing PCE copolymers, especially PCE copolymers that have improved properties as water-reducing agents. Summary of the Invention
[0011] One aspect of the present invention is a polycarboxylic acid ether (PCE) copolymer comprising repeating units derived from:
[0012] (a) 10 to 60 wt% (wt%) of (meth)acrylic acid monomers;
[0013] (b) 30% to 70% by weight of alkyl (meth)acrylate monomers, wherein the alkyl moiety comprises an average of 1 to 3.5 carbon atoms; and
[0014] (c) 5% to 40% by weight of PEG monomers, each of which independently contains:
[0015] (i) the (meth)acrylate moiety, which is linked to (ii) via an ester bond.
[0016] (ii) A polyethylene glycol moiety containing, on average, more than one ethylene oxide unit; and
[0017] (iii) A terminal portion of the polyethylene glycol portion connected at the end opposite to the (meth)acrylate portion, the terminal portion being selected from the hydrogen or alkyl portion; and
[0018] (d) 0% to 20% by weight of other olefinic unsaturated comonomers (“other comonomers”),
[0019] Wherein (i) the weight percentage is based on the total weight of the PCE copolymer, (ii) the PCE copolymer has a comb-like structure comprising an acidic polymer backbone connected to a plurality of dangling polyethylene glycol side chains; and (iii) the weight-average molecular weight (M) of the polycarboxylic acid polymer (referred to as the “hydrolysis product polymer” or “HPP”) resulting from the complete hydrolysis of the ester bonds in the PCE copolymer. w The value is at most 100 kg / mol.
[0020] A second aspect of the present invention is a method for preparing polycarboxylic acid ether (PCE) copolymers, comprising the steps of: emulsion polymerization of the following substances in an aqueous medium containing an emulsified amount of a surfactant and a polymerization initiator, under conditions suitable for producing PCE copolymers:
[0021] (a) 10% to 60% by weight of (meth)acrylic acid monomer;
[0022] (b) 30% to 70% by weight of alkyl (meth)acrylate monomers, wherein the alkyl moiety contains an average of 1 to 3.5 carbon atoms; and
[0023] (c) 5% to 40% by weight of PEG monomers, each of which independently contains:
[0024] (i) the (meth)acrylate moiety, which is linked to (ii) via an ester bond.
[0025] (ii) Polyethylene glycol moieties containing an average of more than one ethylene oxide unit, and
[0026] (iii) A terminal portion of the polyethylene glycol portion connected at the end opposite to the (meth)acrylate portion, the terminal portion being selected from the hydrogen or alkyl portion; and
[0027] (d) 0% to 20% by weight of other comonomers
[0028] The PCE copolymer has a comb-like structure comprising an acidic polymer backbone connected to multiple pendant polyethylene glycol side chains. The weight-average molecular weight (M) of the polycarboxylic acid polymer (referred to as the "hydrolysis product polymer" or "HPP") produced when the ester bonds in the PCE copolymer are completely hydrolyzed is... w The weight percentage is up to 100 kg / mol, where the weight percentage is based on the total weight of the monomer.
[0029] A third aspect of the invention is an aqueous dispersion comprising polymer particles suspended in an aqueous medium, wherein these polymer particles comprise a PCE copolymer as described in the first aspect of the invention.
[0030] A fourth aspect of the present invention is a cementitious mixture comprising the following dry components (a)-(c):
[0031] (a) Packing material;
[0032] (b) Cement;
[0033] (c) At least 0.01% by weight of the PCE copolymer as described in the first aspect of the invention, based on the total weight of the dry components; and
[0034] The optional location also contains water.
[0035] A fifth aspect of the invention is a cured cementitious mixture comprising:
[0036] (a) Packing material;
[0037] (b) hardened cement; and
[0038] (c) The PCE copolymer or its hydrolysis product as described in the first aspect of the invention.
[0039] The PCE copolymers of the present invention can be prepared simply and inexpensively with consistent properties via conventional emulsion polymerization. Emulsion polymerization can use high monomer loadings and produce aqueous dispersions containing high loadings of PCE copolymers. These aqueous dispersions can be effectively used to deliver PCE copolymers as water-reducing agents into cementitious mixtures, or can be effectively spray-dried to form powders. Some PCE copolymers exhibit superior slump properties compared to those prepared by conventional methods. Detailed Implementation
[0040] PCE copolymers and their synthesis
[0041] This invention relates to PCE copolymers. In an acidic environment, the PCE copolymer can exist in a dispersion, wherein the PCE copolymer is contained within dispersed particles suspended in an aqueous medium. In an alkaline environment, the acidic portion of the PCE copolymer is ionized, causing the PCE copolymer to swell and dissolve into the aqueous phase. Depending on the concentration of the dissolved polymer, the viscosity of the aqueous phase can increase.
[0042] For the purposes of this document, "(meth)acrylic acid" means acrylic acid or methacrylic acid, or a mixture of both. In some embodiments, the (meth)acrylic acid monomer is essentially composed of acrylic acid. In some embodiments, the (meth)acrylic acid monomer is essentially composed of methacrylic acid. In some embodiments, the (meth)acrylic acid monomer is a mixture comprising acrylic acid and methacrylic acid, wherein methacrylic acid comprises at least 10% by weight, or at least 20% by weight, or at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 60% by weight, or at least 70% by weight, or at least 80% by weight, or at least 90% by weight. In some embodiments, the (meth)acrylic acid monomer is a mixture comprising acrylic acid and methacrylic acid, wherein acrylic acid comprises at least 10% by weight, or at least 20% by weight, or at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 60% by weight, or at least 70% by weight, or at least 80% by weight, or at least 90% by weight. In some embodiments, the (meth)acrylic acid monomer may also contain small amounts of other alkyl acrylic acids, such as ethyl acrylic acid; in some embodiments, the concentration of other alkyl acrylic acids is at most 10% by weight or at most 5% by weight or at most 2% by weight or at most 1% by weight or substantially 0% by weight (no measurable concentration).
[0043] Similar to (meth)acrylic acid, "(meth)acrylate" refers to an acrylate or a methacrylate, or a mixture of both. The (meth)acrylate monomer may have embodiments equivalent to those described for the (meth)acrylic acid monomer and may contain small amounts of other alkyl acrylates.
[0044] For the purposes of this document, “polyethylene glycol” or “PEG” refers to an oligomer or polymer containing, on average, more than one repeating ethylene oxide unit. Some embodiments of the PEG portion can be expressed as follows:
[0045] -(CR 3 H-CH2-O-) n -
[0046] Where "n" represents an epoxide unit (CHR) 3 The number of -CH2-O-), and each R 3 Independently, it is a hydrogen or lower alkyl group. In the PEG portion, more than 50 molar percentage of the alkyl oxide unit is ethylene oxide, and R 3 On average, it contains less than 0.5 carbon atoms. In some implementations, R 3On average, it contains at most 0.3 carbon atoms, at most 0.2 carbon atoms, at most 0.1 carbon atoms, at most 0.05 carbon atoms, at most 0.02 carbon atoms, or 0.00 carbon atoms. In some embodiments, at least 70 mol% or at least 80 mol% or at least 90 mol% or at least 95 mol% or at least 98 mol% of the epoxide units in the PEG portion are ethylene oxide units. In some embodiments, 100 mol% of the repeating units in the PEG are ethylene oxide units. In some embodiments, the epoxide units other than the ethylene oxide units are selected from propylene oxide units or butane oxide units.
[0047] In some embodiments, the PEG contains, on average, at least 2, 4, 5, 7, 9, 10, 12, 13, 15, 17, or 19 epoxide units. In some embodiments, the PEG contains, on average, at most 50, 45, 40, 30, 25, 23, or 20 epoxide units. Embodiments with the numeral "n" will reflect these embodiments.
[0048] Based on the total weight of the PCE copolymer, the PCE copolymer contains 10% to 60% by weight of repeating units derived from (meth)acrylic acid monomers. In some embodiments, the PCE copolymer contains at least 15% by weight, or at least 18% by weight, or at least 20% by weight, or at least 22% by weight, or at least 24% by weight, or at least 25% by weight, or at least 27% by weight, or at least 28% by weight, or at least 30% by weight, or at least 32% by weight, or at least 35% by weight of repeating units derived from (meth)acrylic acid monomers. In some embodiments, the (meth)acrylic acid monomers primarily comprise (greater than 50% by weight) methacrylic acid.
[0049] Based on the total weight of the PCE copolymer, the PCE copolymer contains 30% to 70% by weight of repeating units derived from alkyl (meth)acrylate monomers. The alkyl (meth)acrylate monomers comprise alkyl moieties linked to the (meth)acrylate moieties via ester moieties. The alkyl moieties of the alkyl (meth)acrylate monomers contain an average of 1.0 to 3.5 carbon atoms. The (meth)acrylate moieties of the alkyl (meth)acrylate monomers have the previously described characteristics.
[0050] In some embodiments, the alkyl moiety contains, on average, at most 3.2 carbon atoms, at most 3.0 carbon atoms, at most 2.8 carbon atoms, at most 2.6 carbon atoms, at most 2.4 carbon atoms, at most 2.2 carbon atoms, or at most 2.0 carbon atoms. In some embodiments, the alkyl moiety contains, on average, at least 1.2 carbon atoms, at least 1.4 carbon atoms, at least 1.6 carbon atoms, at least 1.8 carbon atoms, or at least 2.0 carbon atoms. In some embodiments, the alkyl moiety in at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or up to 100% by weight of the (meth)acrylate monomer is selected from methyl and ethyl groups. In some embodiments, the alkyl moiety in at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or up to 100% by weight of the (meth)acrylate monomer is an ethyl group. In some embodiments, the alkyl moiety in a minority of the (meth)acrylate alkyl monomer may contain three or more carbon atoms, such as propyl, butyl, and hexyl groups. In some embodiments, up to 50% by weight, up to 40% by weight, up to 30% by weight, up to 20% by weight, up to 10% by weight, or 0% by weight of the (meth)acrylate alkyl monomer contains three or more carbon atoms in its alkyl moiety.
[0051] Examples of suitable alkyl methacrylate monomers include methyl acrylate, ethyl acrylate, methyl methacrylate, and ethyl methacrylate. In some embodiments, the alkyl methacrylate monomer comprises primarily (greater than 50% by weight) ethyl acrylate or at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or up to 100% by weight of ethyl acrylate. In some embodiments, the alkyl methacrylate monomer may comprise a mixture of alkyl methacrylate monomers, and in some embodiments, the alkyl methacrylate monomer consists essentially of a single monomer.
[0052] In some embodiments, the PCE copolymer contains at least 32% by weight, or at least 34% by weight, or at least 36% by weight, or at least 38% by weight of repeating units derived from alkyl (meth)acrylate monomers. In some embodiments, the PCE copolymer contains at most 65% by weight, or at most 60% by weight, or at most 55% by weight, or at most 52% by weight, or at most 50% by weight, or at most 48% by weight, or at most 45% by weight of repeating units derived from alkyl (meth)acrylate monomers.
[0053] Based on the total weight of the PCE copolymer, the PCE copolymer contains 5% to 40% by weight of repeating units derived from "PEG monomer". The PEG monomer contains (i) a (meth)acrylate moiety linked via an ester bond to (ii), (ii) a polyethylene glycol moiety containing an average of more than one ethylene oxide unit, and (iii) a terminal portion of the polyethylene glycol moiety linked at the end opposite the (meth)acrylate moiety, the terminal portion being selected from hydrogen or alkyl moieties. Formula 1 illustrates an exemplary PEG monomer:
[0054]
[0055] in:
[0056] • Each R 1 Independently a hydrogen or alkyl group, wherein the alkyl group is selected such that R 1 On average, it contains fewer than 2 carbon atoms;
[0057] • Each R 2 Independently a terminal portion selected from hydrogen or alkyl groups; and
[0058] • Each R 3 Independently hydrogen or a lower alkyl group, the lower alkyl group being selected such that R 3 On average, it contains less than 0.5 carbon atoms, as previously stated;
[0059] •-(CHR 3 -CH2O) n - is the polyethylene glycol portion, as previously described, comprising n repeating epoxide units, where n is on average greater than 1.
[0060] In some embodiments, the meth(acrylate) moiety of the PEG monomer primarily comprises (greater than 50% by weight) the acrylate moiety (R... 1 =H). In some embodiments, the meth(acrylate) moiety of the PEG monomer primarily comprises (greater than 50% by weight) the methacrylate moiety (R). 1 =-CH3). In some implementations, R 1 On average, it contains at most 1.2 carbon atoms, at most 1.0 carbon atoms, at most 0.8 carbon atoms, at most 0.6 carbon atoms, at most 0.4 carbon atoms, or at most 0.2 carbon atoms. In some embodiments, R 1 On average, it contains at least 0.2 carbon atoms, at least 0.4 carbon atoms, at least 0.6 carbon atoms, at least 0.8 carbon atoms, or at least 1.0 carbon atoms.
[0061] Polyethylene glycol portion, R 3 The implementation schemes for n are as previously described.
[0062] The polyethylene glycol portion of the PEG monomer has an end portion (R) opposite to the methyl (acrylate) portion. 2 End capping. In some implementations, the end portion is a hydrogen atom (R... 2 =H). In some embodiments, the terminal portion is an alkyl group (R). 2 =alkyl). Terminal portion (R) 2 The alkyl group in ) contains at least one carbon atom. In some embodiments, the terminal portion (R) 2 The alkyl groups in the ) contain an average of at most 24 carbon atoms, at most 22 carbon atoms, at most 20 carbon atoms, at most 18 carbon atoms, or at most 16 carbon atoms. In some embodiments, the terminal portion (R) 2 The alkyl group in () is a lower alkyl group, meaning that the alkyl group contains, on average, less than 8 carbon atoms or at most 6 carbon atoms or at most 4 carbon atoms or at most 2 carbon atoms. In some embodiments, the terminal portion (R) 2 The alkyl groups in the PEG monomer are aliphatic alkyl groups, meaning that the alkyl groups contain an average of at least 8 carbon atoms, at least 10 carbon atoms, at least 12 carbon atoms, or at least 14 carbon atoms. In some embodiments, the end groups on the PEG monomer contain a mixture of lower alkyl groups and aliphatic alkyl groups.
[0063] In some embodiments, the PEG monomer is selected such that it is moderately hydrophilic but also moderately lipophilic, and that it interacts with the oil phase during emulsion polymerization. In some embodiments, the PEG monomer is selected such that the resulting PCE copolymer is insoluble in acidic aqueous media but soluble in alkaline aqueous media. PEG chains that contain virtually no propylene oxide or butane oxide units are generally hydrophilic. When the PEG monomer contains a number of repeating alkyl oxide units (e.g., when n averages at least 10, at least 15, or at least 20), in some embodiments, it can be achieved by adding R... 2 The PEG monomer has aliphatic end groups and / or is made more lipophilic by incorporating propylene oxide or butane oxide into the PEG chain. On the other hand, when the PEG monomer contains only a small number of alkylene oxide units (such as when n averages at most 10, 15, or 20), in some embodiments the PEG chain contains almost no propylene oxide or butane oxide, and / or the terminal portion (R... 2 It contains hydrogen or lower alkyl groups.
[0064] In some embodiments, the PEG monomer has a number average molecular weight of at least 150 g / mol, at least 200 g / mol, at least 300 g / mol, at least 400 g / mol, at least 450 g / mol, or at least 500 g / mol. In some embodiments, the PEG monomer has a number average molecular weight of at most 3000 g / mol, at most 2000 g / mol, at most 1000 g / mol, at most 900 g / mol, at most 800 g / mol, or at most 750 g / mol.
[0065] In some embodiments, the PCE copolymer contains at least 6 wt%, at least 7 wt%, at least 10 wt%, at least 12 wt%, or at least 13 wt% of repeating units derived from PEG monomers. In some embodiments, the PCE copolymer contains at most 38 wt%, at most 35 wt%, at most 30 wt%, at most 25 wt%, at most 20 wt%, at most 18 wt%, at most 16 wt%, or at most 14 wt% of repeating units derived from PEG monomers.
[0066] Based on the total weight of the PCE copolymer, the PCE copolymer may optionally contain 0% to 20% by weight of repeating units derived from other olefinic unsaturated comonomers. Examples of suitable “other olefinic unsaturated comonomers” include maleic acid, itaconic acid, styrene, vinyl acetate, vinyl alcohol, acrylonitrile, acrylamide, alkylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, sodium styrene sulfonate, sodium vinyl sulfonate, ethyl methacrylate, and vinyl chloride. In some embodiments, the PCE copolymer contains up to 15% by weight, up to 10% by weight, up to 5% by weight, up to 3% by weight, or up to 2% by weight of repeating units derived from other comonomers. In some embodiments, the PCE copolymer may be substantially free of repeating units derived from other comonomers (0% by weight).
[0067] Suitable (meth)acrylic acid monomers, (meth)acrylic acid alkyl ester monomers, PEG monomers, and other comonomers are commercially available. PEG monomers can also be prepared by known methods, such as the reaction of (meth)acryloyl chloride with polyethylene glycol as described in the following literature: Lin-Gibson et al., “Synthesis and Characterization of PEGDimethacrylates and Their Hydrogels”, 5(4). Biomacromolecules 1280-1287 (2004) and Takeshita et al., “Crystallization of graft copolymers 1.Graft Chains Misciblewith Main Chains” 42 Polymer Journal 482-488 (2010).
[0068] In some embodiments, the PCE copolymer is a random copolymer. In some embodiments, the PCE copolymer is represented by Formula 2:
[0069]
[0070] in:
[0071] • Each R is independently an alkyl group derived from a repeating unit of a (meth)acrylate monomer, as previously described;
[0072] • Each R 1 Independently hydrogen or an alkyl group as described above;
[0073] • Each R 2 Independently hydrogen or an alkyl group at the end of the PEG moiety as previously described;
[0074] •-(CHR 3 -CH2O) n - The PEG portion, as previously described, contains n repeating epoxide units;
[0075] • Each R 3 Independently hydrogen or a lower alkyl group as described above;
[0076] • Each M is independently a substituent suitable for other olefinic unsaturated comonomers as previously described, such as hydroxyl moiety, amide moiety, alkylamide moiety, nitrile moiety, halide moiety, acetate moiety, organic sulfonate moiety or organic phosphate moiety;
[0077] •x represents the number of repeating units derived from (meth)acrylic acid monomers, averaging 10% to 60% by weight of the polymer;
[0078] •y represents the number of repeating units derived from (meth)acrylate monomers, averaging 30% to 70% by weight of the polymer;
[0079] •z represents the number of repeating units derived from the PEG monomer, averaging 5% to 40% by weight of the polymer;
[0080] •m represents the number of repeating units derived from other comonomers, averaging from 0% to 20% by weight of the polymer; and
[0081] • End groups on the polymer backbone are not shown.
[0082] In some embodiments of Equation 2, the repeating units shown are randomly distributed within the polymer. R, R 1R 2 R 3 The implementation schemes for M, x, y, z, n, and m are as described above.
[0083] As shown in Formula 2, the PCE copolymer comprises a poly(carboxylic acid) polymer backbone (“acid polymer backbone”). The dangling alkyl groups and polyethylene glycol (PEG) moieties are linked to the acid polymer backbone via ester bonds. This structure is sometimes referred to as a “comb” structure, as previously described.
[0084] As previously described, the dangling alkyl and polyethylene glycol (PEG) moieties can be removed from the acidic polymer backbone of a PCE copolymer by hydrolysis to obtain a poly(carboxylic acid) polymer, referred to as a "hydrolysis product polymer" or "HPP". An example of HPP is shown in Formula 3:
[0085]
[0086] Where x, y, z, m, M and R 1 The values correspond to those in the PCE copolymer, and the end groups on the polymer backbone are not shown. The expected molecular weight distribution of HPP is approximately equal to the stoichiometric distribution of the acidic polymer backbone in the PCE copolymer.
[0087] In some embodiments, the weight-average molecular weight of the polycarboxylate polymer (HPP) resulting from the complete hydrolysis of the ester bonds in the PCE copolymer is at most 95 kg / mol, or at most 90 kg / mol, or at most 85 kg / mol, or at most 80 kg / mol, or at most 75 kg / mol, or at most 70 kg / mol, or at most 68 kg / mol, or at most 65 kg / mol, or at most 55 kg / mol, or at most 50 kg / mol, or at most 45 kg / mol, or at most 40 kg / mol, or at most 35 kg / mol, or at most 30 kg / mol. In some embodiments, the weight-average molecular weight of the HPP is at least 10 kg / mol, or at least 12 kg / mol, or at least 15 kg / mol, or at least 18 kg / mol, or at least 20 kg / mol. (Molecular weight data in this document refer to relative molecular weights. See the test method description for more information.)
[0088] In some implementations, the number-average molecular weight (M) of HPP is... n The number-average molecular weight (Mn) of HPP is at most 30 kg / mol, or at most 25 kg / mol, or at most 22 kg / mol, or at most 20 kg / mol, or at most 18 kg / mol, or at most 15 kg / mol, or at most 12 kg / mol, or at most 10 kg / mol. In some embodiments, the number-average molecular weight (Mn) of HPP is... nThe value is at least 3 kg / mol, or at least 4 kg / mol, or at least 5 kg / mol, or at least 6 kg / mol, or at least 7 kg / mol.
[0089] In some implementations, the dispersion (M) of HPP w / M n The value is at most 6.0 or at most 5.5 or at most 5.0 or at most 4.5 or at most 4.0 or at most 3.8 or at most 3.5 or at most 3.3. In some implementations, the dispersion (M) of HPP is... w / M n () is at least 2.0 or at least 2.5 or at least 2.7 or at least 2.8 or at least 2.9.
[0090] In some embodiments, the growth of the acidic polymer backbone is restricted during emulsion polymerization by using a chain transfer agent. In this case, at least one end of the acidic polymer backbone can be capped by residues of the chain transfer agent. For example, PCE copolymers can conform to Formula 4:
[0091]
[0092] Where A is a residue of the chain transfer agent, and all other parts have the meaning defined for Formula 2. In some embodiments, A is composed of formula (-SR) 4 ) indicates that R 4 It includes an aliphatic portion. In some implementations, R 4 The hydrocarbon group moiety, such as an alkyl group. In some embodiments, R 4 It contains oxygen, such as in ketones, alcohols, carboxylic acids, or carboxylic esters. In some embodiments, R 4 It contains at least two carbon atoms or at least three carbon atoms. In some embodiments, R 4 It contains at most 24 carbon atoms, or at most 20 carbon atoms, or at most 18 carbon atoms, or at most 16 carbon atoms, or at most 14 carbon atoms, or at most 12 carbon atoms, or at most 10 carbon atoms, or at most 8 carbon atoms, or at most 6 carbon atoms, or at most 4 carbon atoms. In some embodiments, A is derived from the formula (-OR 4 -R 4 -X or simply R 4 It means that R 4 As previously described, and X is a halogen, such as chlorine or iodine.
[0093] In some embodiments, the monomers are selected such that the PCE copolymer is alkali-soluble, meaning it is soluble in water at pH 10, as measured according to the test method. The cementitious environment is alkaline. In some embodiments, the PCE copolymer dissolves in the cementitious environment. In some embodiments, the PCE copolymer has a solubility of at least 1 g / 100 g in water at pH 10. In some embodiments, the PCE copolymer has a solubility of at least 10 g / 100 g, at least 20 g / 100 g, or at least 30 g / 100 g in water at pH 10. The solubility limits of some PCE copolymers may be difficult to measure because the viscosity of the solution increases with increasing PCE copolymer concentration.
[0094] In some embodiments, the monomers are selected such that the resulting PCE copolymer remains a stable dispersion in aqueous acidic environments, such as in water with a pH of at most 6.5, 5.5, 5.0, 4.5, 4.0, 3.5, or 3.0. The ability to remain a dispersion is influenced by the balance between the hydrophilic and lipophilic portions of the polymer. The selection and ratio of acids, acrylates, and PEG monomers can affect the hydrophilic and lipophilic balance of the PCE copolymer (as previously described) and its ability to remain in a stable dispersion.
[0095] The PCE copolymer of the present invention is prepared by emulsion polymerization. Emulsion polymerization is a well-known method and is described in many publications, such as those published by Rohm and Haas Company. Emulsion Polymerization of Acrylic Monomers (1966), available https: / / ia600709.us.archive.org / 35 / items / emulsionpolymeri00rohm / emulsionpolymeri00rohm.pdf Accessed by: Lovell et al., Fundamentals of Emulsion Polymerization, 21 Biomacromolecules 4396-4441 (2020); and Juaregui, Thesis: Synthesis and Optimization of Emulsion Polymers, California Polytechnic State University, San Luis Obispo (2016).
[0096] Emulsion polymerization is carried out in an aqueous medium containing a surfactant that acts as an emulsifier. The monomer and surfactant form a dispersed organic phase in the aqueous medium, and the polymerization is initiated by a free radical initiator or a redox initiator. The selection and proportion of monomers in emulsion polymerization reflect their desired proportions in the resulting polymer, as previously described. In some embodiments, the monomer emulsion contains at least 15% by weight, or at least 20% by weight, or at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 60% by weight, based on the total weight of the monomer emulsion. In some embodiments, the monomer emulsion contains at most 70% by weight, or at most 60% by weight, or at most 50% by weight, based on the total weight of the monomer emulsion.
[0097] An example of a suitable surfactant used as an emulsifier is the trademark DOWFAX. ™ and TRITON ™ Available commercially from The Dow Chemical Company. See, for example, "Solutions for Emulsion Polymerizations," published by Dow Chemical Company (2018). In some embodiments, the weight percentage of the emulsifier to the monomer is at least 0.1 wt%, at least 0.2 wt%, at least 0.5 wt%, at least 1.0 wt%, or at least 1.5 wt%. In some embodiments, the weight ratio of the emulsifier to the monomer is at most 3.0 wt%, at most 2.5 wt%, or at most 2.0 wt%.
[0098] Initiators for emulsion polymerization are known and commercially available. In some embodiments, the initiator is a water-soluble free radical initiator. Examples of free radical initiators include persulfates (such as ammonium persulfate and sodium persulfate) and water-soluble azo compounds, such as 2,2'-azobis[2-methylpropanediamine] dihydrochloride and 4,4'-azobis[4-cyanopentanoic acid]. In some embodiments, the initiator-to-monomer weight ratio is at least 0.05% by weight, at least 0.1% by weight, or at least 0.15% by weight. In some embodiments, the initiator-to-monomer weight ratio is at most 1% by weight or at most 0.5% by weight.
[0099] Polymerization is carried out under conditions suitable for limiting the growth of the acidic polymer backbone, as previously described. Known methods for controlling chain growth include the use of chain transfer agents, atom transfer radical polymerization (ATRP), reversible addition / fragmentation chain transfer polymerization (RAFT), or nitrile-oxygen mediated polymerization. See, for example, Cunningham, “Living / Controlled Radical Polymerizations in Dispersed Phase Systems,” 27 Pro, Poly, Sci. 1039-1067 (2002) and “Sigma-Aldrich Controlled Radical Polymerization Guide,” published by Merck KGaA (2019).
[0100] In some embodiments, emulsion polymerization is carried out in the presence of a chain transfer agent. Chain transfer agents and their uses are well known. See, for example, K. Matyjaszewski and T. Davis, Handbook of Radical Polymerization Chapter 12, “Control of Free Radical Polymerization by ChainTransfer Methods” 629-691 (2002). Examples of suitable chain transfer agents include thiols, disulfides, alcohols, and haloalkyl compounds. In some embodiments, the chain transfer agent is represented by Formula 5:
[0101]
[0102] Where R 4 As previously described. Examples of suitable chain transfer agents are methyl mercaptopropionate, mercaptopropionic acid, butyl mercaptopropionate, 2-mercaptoethanol, octylthiol, and dodecanethiol, which are commercially available.
[0103] The amount of chain transfer agent is suitable for limiting the growth of the acidic polymer backbone, as previously described. In some embodiments, the reaction mixture contains at least 0.2 wt%, at least 0.4 wt%, at least 0.5 wt%, at least 0.6 wt%, at least 0.7 wt%, at least 0.8 wt%, at least 0.9 wt%, or at least 1.0 wt% of chain transfer agent based on the total weight of monomers in the reaction mixture. In some embodiments, the reaction mixture contains at most 5.0 wt%, at most 4.0 wt%, at most 3.0 wt%, at most 2.0 wt%, at most 1.8 wt%, at most 1.6 wt%, at most 1.4 wt%, or at most 1.2 wt% of chain transfer agent based on the total weight of monomers in the reaction mixture.
[0104] In some embodiments, emulsion polymerization is carried out at temperatures of at least 30°C, at least 40°C, at least 50°C, at least 60°C, at least 70°C, or at least 75°C. In many embodiments, emulsion polymerization is carried out at temperatures of up to 95°C or up to 90°C. Pressure is not critical, as long as the blend of water, emulsifier, and other components is stable; in most embodiments, ambient pressure is convenient. In many embodiments, the reaction mixture is stirred to provide good mixing.
[0105] The result of emulsion polymerization is a polymer dispersion containing PCE copolymer particles suspended in an aqueous solvent. In some embodiments, an emulsifier from the emulsion polymerization participates in stabilizing the dispersion. In some embodiments, the Z-mean diameter of the polymer particles is at least 50 nm, at least 70 nm, or at least 90 nm. In some embodiments, the Z-mean particle size is at most 500 nm, at most 250 nm, at most 150 nm, or at most 100 nm. In some embodiments, the dispersion is a colloidal dispersion.
[0106] In some implementations, the aqueous dispersion produced by polymerization can be modified, such as by adding water or other solvents, by adding dispersants or other additives, or by adding acids, bases or buffers to adjust the pH.
[0107] The aqueous medium in the aqueous dispersion contains at least 50% by weight of water based on the weight of the aqueous medium. In some embodiments, the aqueous medium contains at least 60% by weight, or at least 70% by weight, or at least 80% by weight, or at least 90% by weight, or at least 95% by weight, or 100% by weight of water based on the weight of the aqueous medium. Other components of the aqueous medium, if any, should be miscible with water and should not cause the PCE copolymer to dissolve in the acidic aqueous medium.
[0108] In some embodiments, the dispersion is stable at 25°C for at least 1 day, at least 1 week, at least 1 month, at least 2 months, at least 3 months, or at least 6 months. In this context, "stable" means that the dispersion does not exhibit visible phase separation, particle aggregation, or agglomeration.
[0109] In some embodiments, the pH of the dispersion is at most 6.5, or at most 6.0, or at most 5.5, or at most 5.0, or at most 4.5, or at most 4.0, or at most 3.5. In some embodiments, the pH of the dispersion is at least 2.0 or at least 2.5. Generally, higher pH can lead to the dissolution and / or gelation of the PCE copolymer.
[0110] In some embodiments, the concentration of the PCE copolymer in the polymer dispersion is at least 10% by weight, or at least 15% by weight, or at least 20% by weight, or at least 25% by weight, or at least 27% by weight, or at least 29% by weight. In some embodiments, the concentration of the PCE copolymer in the polymer dispersion is at most 50% by weight, or at most 45% by weight, or at most 40% by weight.
[0111] In some implementations, PCE copolymers can be stored and used as polymer dispersions.
[0112] In some embodiments, the polymer dispersion can be spray-dried or freeze-dried to form a powder containing the PCE copolymer. Spray drying equipment is commercially available and comes with instructions for use, and spray drying is described in many publications, such as: Santos et al., “Spray Drying - A Overview,” available at: http: / / dx.doi.org / 10.5772 / intechopen.72247 Obtain from: Bete Performance Spray Engineering's "Spray Dry Manual" published at www.BETE.com; and More Swati et al., "Review on Spray Drying Technology" 4(2). IJPCBS 219-225 (2014). PCE copolymer powder is easier to store and transport, and can optionally be added to the dry mixture before water is added.
[0113] Uses as a water-reducing agent
[0114] The PCE copolymer of the present invention can be used as a water-reducing agent in cementitious mixtures (dry or wet mixtures). The powder containing the PCE copolymer can be added to the dry mixture before water is added. Alternatively, the powder or dispersion containing the PCE copolymer can be added to the wet mixture after water is added. Alternatively, the powder or dispersion containing the PCE copolymer can be added to water before water is added to the dry mixture.
[0115] Cementitious mixtures contain fillers, cement, and optional other additives as dry components. ("Dry component" refers to any component of a cementitious mixture that is normally solid at up to 40°C and atmospheric pressure.)
[0116] Fillers for cementitious mixtures typically contain inorganic particles. The particle size of the filler varies depending on the intended use of the cementitious mixture. Mortar, grout, and stucco fillers typically contain sand. US standards for masonry fillers are listed in ASTM C144 and AASHTO M 45-15 / ASTM C 144-11. Concrete fillers typically contain aggregates, mixtures of sand and gravel of various sizes. US standards for concrete aggregate fillers are listed in ASTM C33 and AASHTO M 6 / M 80. See also Kousmata et al. Design and Control of Concrete Mixtures Chapter 6, “Aggregates for Concrete” (2016). In some embodiments, the filler may also contain volcanic ash, such as fly ash, calcined kaolin, pumice, or pyrolytic silica; volcanic ash and its use in cementitious mixtures are well known and described in U.S. Patent 9,181,131,B2. In some embodiments, the filler may also contain inorganic pigments, such as titanium dioxide, other metal oxides, or carbon black. In some embodiments, the filler may also contain organic fibers or particles.
[0117] In some embodiments, the cementitious mixture, excluding water, contains at least 50% by weight, at least 60% by weight, at least 65% by weight, or at least 70% by weight of filler, based on the dry component. In some embodiments, the cementitious mixture, excluding water, contains at most 85% by weight or at most 80% by weight of filler, based on the dry component. In some embodiments, the cementitious mixture, excluding water, contains at least 50% by volume, at least 55% by volume, or at least 60% by volume of filler, based on the dry component. In some embodiments, the cementitious mixture, excluding water, contains at most 85% by volume, at most 80% by volume, or at most 75% by volume of filler, based on the dry component.
[0118] ASTM recognizes five types of cement: Type 1 (ordinary Portland cement); Type 2 (medium sulfate-resistant cement); Type 3 (rapid-hardening cement); Type 4 (low-heat cement); and Type 5 (high sulfate-resistant cement). Blends and variations of these five types are also available, such as Portland limestone cement (Type 1L). Any of these cements, blends, or variations can be used in the cementitious mixtures of this invention. In some embodiments, the cement is ordinary Portland cement. In some embodiments, the cement is a variant of ordinary Portland cement, referred to as white cement. In some embodiments, the cement is Portland limestone cement. In some embodiments, the cement is a more specialized cement, such as high alumina cement or calcium sulfoaluminate cement. Suitable cements are commercially available.
[0119] The cementitious mixture should contain sufficient cement to effectively bind the dry components together. In some embodiments, based on the dry components and excluding water, the cementitious mixture contains at least 15% by weight or at least 20% by weight of cement. In some embodiments, based on the dry components and excluding water, the cementitious mixture contains at most 50% by weight or at most 40% by weight or at most 35% by weight or at most 30% by weight of cement.
[0120] Examples of other additives that may be optionally included in cementitious mixtures include water-retaining agents, starch ethers, rheology modifiers, air-entraining agents, accelerators, retarders, and defoamers.
[0121] • Water-retaining agents, such as cellulose ethers, slow down the separation of water from the wet mixture.
[0122] • Starch ethers, such as hydroxypropyl starch ether, can improve the anti-sag and anti-slip properties of wet mixtures, as well as extend open time and provide a smoother surface.
[0123] • Rheology modifiers, such as bentonite, organically modified clay, attapulgite, pyrolytic silica, and precipitated calcium carbonate, can alter the viscosity and shear-thinning behavior of wet mixtures.
[0124] • Air-entraining agents cause the formation of small bubbles in the wet mixture, which can improve the resilience of the cured mixture under freeze-thaw cycles. Air-entraining agents are typically surfactants.
[0125] • Accelerators speed up the solidification of wet mixtures. They can be especially useful in cold weather applications. Examples of common accelerators include calcium nitrate, calcium nitrite, calcium formate, and certain aluminum compounds.
[0126] • Retarder slows down the setting time of wet mixtures. Examples of common retarders include lignin sulfonic acid, hydroxycarboxylic acid, carbohydrates, lead oxide, zinc oxide, phosphates, borates, and calcium, sodium, and ammonium salts of fluorides.
[0127] • Defoamers reduce air entrainment and voids in wet mixtures. Examples of defoamers include mineral oil, polyethylene glycol, and polyether siloxanes.
[0128] The aforementioned additives are commercially available along with their instructions for use.
[0129] In some embodiments, based on the dry component and excluding water, the cementitious mixture contains at most 10% by weight, at most 5% by weight, or at most 2% by weight of other additives. In some embodiments, based on the weight of the dry component excluding water, the cementitious mixture contains an immeasurable amount (essentially 0% by weight) or at least 1% by weight or at least 2% by weight of other additives. In some embodiments, the wet mixture contains at least 10 ppm, at least 25 ppm, at least 40 ppm, or at least 50 ppm of defoamer based on the total weight of the wet mixture. In some embodiments, the wet mixture contains at most 500 ppm, at most 200 ppm, at most 100 ppm, or at most 75 ppm of defoamer based on the total weight of the wet mixture.
[0130] The cementitious mixture contains an appropriate amount of the PCE copolymer of the present invention to reduce the amount of water required to produce a wet mixture with suitable processability. In some embodiments, the cementitious mixture contains at least 0.05 wt%, at least 0.08 wt%, at least 0.10 wt%, at least 0.1 wt%, at least 0.15 wt%, at least 0.2 wt%, at least 0.25 wt%, or at least 0.3 wt% of the PCE copolymer based on the total weight of cement. In some embodiments, the cementitious mixture contains at most 1.0 wt%, at most 0.8 wt%, at most 0.6 wt%, at most 0.5 wt%, at most 0.4 wt%, or at most 0.3 wt% of the PCE copolymer based on the total weight of cement.
[0131] In some embodiments, some or all of the dry components are pre-blended to form a dry mixture before being mixed with water to form a wet mixture. In some embodiments, some dry components, particularly additives, may be omitted from the dry mixture and may be added to water before being blended to form a wet mixture, or may be added to the wet mixture after it has been formed.
[0132] To prepare the wet mixture, water is blended with the dry components in an amount sufficient to completely wet them, providing a homogeneous cementitious mixture with desired workability and viscosity. The optimal amount of water varies depending on the dry components and their intended use, and can be readily determined experimentally. In some embodiments, the amount of water is at least 9% by weight, at least 10% by weight, at least 11% by weight, or at least 12% by weight, based on the total weight of the wet mixture. In some embodiments, the amount of water is at most 30% by weight, at most 25% by weight, at most 22% by weight, at most 20% by weight, at most 18% by weight, at most 16% by weight, at most 15% by weight, at most 14% by weight, at most 13% by weight, or at most 12% by weight, based on the total weight of the wet mixture.
[0133] In some embodiments, compared to the same wet mixture without water-reducing agents, the wet mixture containing PCE copolymers requires at least 5%, at least 8%, at least 10%, at least 12%, at least 15%, at least 20%, at least 25%, or at least 30% less water to reach processable viscosity.
[0134] In some embodiments, the slump of the wet mixture immediately after preparation (T0, measured according to test methods) is at least 25 mm greater, or at least 30 mm greater, or at least 40 mm greater, or at least 50 mm greater, or at least 60 mm greater, or at least 70 mm greater, or at least 80 mm greater, or at least 90 mm greater, or at least 100 mm greater than the slump of a similar wet mixture without PCE copolymer. In some embodiments, the wet mixture is slumped 30 minutes after preparation (T0, measured according to test methods). 30 The slump (measured according to the test method) showed a similar improvement.
[0135] The wet mixture can be used in any suitable application. For example:
[0136] • Wet concrete mixtures can be cured in molds or templates to form solid structures such as pavements, paving stones, floors, blocks, walls, columns or other concrete products.
[0137] • Mortar can hold bricks, blocks, tiles or other structural elements in place.
[0138] • Plaster can be applied to walls or formed as a layer in an exterior wall insulation and finishing (EIFS) system.
[0139] After application, the wet mixture is allowed to dry and cure. The time required for drying and curing varies significantly depending on the selection of dry components in the wet mixture (such as cement, accelerators, and retarders), the amount of water, the thickness of the application, and the temperature and humidity during drying and curing. In many implementations, cementitious mixtures are touch-dry in a few hours or less and can bear weight within a day or two. On the other hand, curing to full strength may take many days.
[0140] Upon completion of curing, the cured cementitious mixture reflects the content of the wet mixture used to prepare it. The cured cementitious mixture contains filler, cured cement, optional additives, and residual PCE copolymers of the present invention or their reaction products. In some embodiments, the alkaline environment of the wet mixture hydrolyzes the ester bonds in the PCE copolymer and releases PEG side chains. Therefore, some or all of the PEG side chains can be removed from the PCE copolymer. The released PEG polymer can migrate to other parts of the wet mixture and can be trapped there in the cured cementitious mixture. Similarly, some or all of the acidic polymer backbone can have its side chains partially or completely removed, and it contains a higher level of dangling acid moiety than the original PCE copolymer.
[0141] Test methods
[0142] Unless otherwise stated, the measurements listed in this application are performed using the following test methods:
[0143]
[0144] HPP was obtained by hydrolysis of PCE copolymer. :
[0145] The PCE copolymer sample was hydrolyzed in a Parr Bomb 4749 acid digestion vessel to obtain the hydrolysate polymer (HPP). Hydrolysis was performed by adding 0.50 g of PCE copolymer, 1 g of potassium hydroxide granules, 0.25 g of deionized water, and 10 mL of ethanol to a Teflon cup. The Teflon cup containing the aforementioned materials was placed in the acid digestion vessel and sealed according to the manufacturer's instructions. The sealed acid digestion vessel was placed in an oven at 150°C for 3 days. The Teflon cup was then removed from the acid digestion vessel, and the supernatant was discarded. Solid HPP was collected from the bottom of the cup and rinsed with 10 mL of ethanol. This solid HPP was then used for molecular weight distribution analysis.
[0146] The molecular weight of HPP The molecular weight of HPP was determined by size exclusion chromatography (SEC).
[0147] Sample preparation of HPP solution: HPP was mixed at a concentration of 2 mg / g in a phosphate buffer solution containing 20 mM (1:1 NaH2PO4 and Na2HPO4) at a pH of 7.0. The mixture was shaken overnight at room temperature on a mechanical shaker to completely dissolve the HPP. Next, the sample solution was filtered using a 0.2 μm Target2 (Fisher) PVDF filter. The sample was visually inspected to ensure no visible undissolved material was present.
[0148] HPP was separated into different molecular weight fractions using a Waters UPLC system via SEC. This system features an isocratic pump, degasser, injector, column oven, and RI detector operating at 35°C. The UPLC system was equipped with TOSOH Bioscience TSKgel G2500PWxl and TSKgel GMPWxl columns (packed with 7µm and 13µm particles, internal dimensions 7.8mm × 300mm). The system was calibrated using sodium polyacrylate from American Polymer Standards Corporation. 20μL of sample was injected, and the mobile phase flow rate was maintained at 1.0ml / min. Data were collected and processed using Empower software version 3 (Waters, Milford, MA). (For clarity, the molecular weights reported by this system are relative molecular weights, not absolute molecular weights, based on the sodium polyacrylate standard.)
[0149] Example
[0150] The following examples illustrate specific implementations of the present invention, but do not limit the widest scope of the invention.
[0151] The materials in Table 1 are used in the examples:
[0152] Table 1
[0153]
[0154]
[0155] Polymer Synthesis
[0156] The monomers listed in Table 2 were subjected to emulsion polymerization as follows: SLS (12.60 g, 28% by weight aqueous solution) and water (579.38 g) were placed in a 3 L four-necked round-bottom flask equipped with a water condenser, a top stirrer and a thermocouple, and heated to 88 °C under nitrogen.
[0157] Monomer emulsions were prepared by mixing SLS (8.40 g, 28% by weight aqueous solution) and water (195 g) together in a wide-mouth glass flask at ambient temperature. The desired monomers, as shown in Table 2, were added in the following order:
[0158] • Acrylate monomers containing dissolved MMP,
[0159] •PEG monomers,
[0160] • Methacrylic acid monomer (MAA).
[0161] The monomer weight ratios for each embodiment were selected to reflect the proportions shown in Table 2, and the total mass of monomers was selected to provide a final PCE copolymer dispersion with the solids content shown in Table 2. A portion of the monomer emulsion (41.18 g) was added to a round-bottom flask while stirring. Immediately after adding the monomer emulsion, a mixture of APS initiator (0.53 g in 11.25 g water) was added to the vessel, followed by rinsing with water (3.75 g). At the exothermic peak, an aqueous APS solution (0.23 g in 45 g water) and the remaining monomer emulsion were added to the round-bottom flask over 1.5 hours while maintaining the contents at 85°C. After 1.5 hours, the container and feed line of the monomer emulsion and APS were rinsed with water, and the reaction mixture was stirred at 85°C for 5 minutes. An aqueous APS solution (0.19 g in 48.75 g water) was added over 15 minutes. The contents were cooled to 75°C, and dilution water (15 g) was added.
[0162] Continue cooling to 30°C. During cooling, remove any remaining free monomers from the round-bottom flask by adding 0.15 wt% (2.74 g) of an aqueous solution of active ferrous sulfate heptahydrate. Then, over 15 minutes, add an aqueous solution of 70% tert-butyl hydroperoxide (0.3 g diluted in 9.38 g of water) and rinse with water (1.88 g). Simultaneously, add isoascorbic acid (0.41 g dissolved in 9.38 g of water) for another 15 minutes, and rinse with additional water (1.88 g). Then, repeat the addition of tert-butyl hydroperoxide and isoascorbic acid once more as described above.
[0163] The final polymer dispersion was filtered sequentially through 100-mesh and 325-mesh sieves. The approximate solid content of the polymer dispersion is shown in Table 2, and the pH of the polymer dispersion ranged from 2.5 to 4.
[0164] The particle size of the polymer particles in the dispersion was measured according to the test method described. The results are shown in Table 2.
[0165] Hydrolysis of PCE copolymers :
[0166] The PCE copolymer sample was hydrolyzed into HPP, and the molecular weight distribution of HPP was measured according to the test method. The results are shown in Table 2.
[0167] Production of PCE powder
[0168] The dispersion samples from IE1, IE2, and CE3 were spray-dried to produce PCE copolymer powder. The polymer dispersion was diluted to a solid content of 15% to 20% by weight. The diluted dispersion was spray-dried using a GEA Mobile Miner spray dryer equipped with a dual-fluid nozzle atomizer. The inlet and outlet temperatures were set to 120°C to 125°C and 55°C to 65°C, respectively. The nitrogen (N2) pressure at the nozzle was set to 1 bar, and the flow rate was 50%, equivalent to an air flow rate of 6 kg / h. The diluted polymer dispersion was introduced into the spray dryer via a peristaltic pump. The water content in the atomized droplets was rapidly evaporated by contact with the hot N2 stream at the inlet temperature. The dried powder was then cooled to the outlet temperature. A cyclone separator in the spray dryer separated the dried polymer powder from the N2 stream therein. Residual powder was filtered before aeration.
[0169] Aqueous dispersion samples from IE3-IE9 and IE12-IE13 were freeze-dried to produce PCE copolymer powders. Each dispersion was placed in a -20°C freezer for 2 days, and then placed in a LABCONCO FreeZone 4.5L instrument at -50°C for 3 days with a vacuum setting of 0.01 Torr and a condenser setting of -50°C.
[0170]
[0171] Mortar production and testing
[0172] According to ASTM C305, a mortar mix is prepared by mixing 1L of type cement, sand, defoamer, and water in a 6L container using a KitchenAid mixer at a scale of 2000g. The weight ratio of 1L type cement to sand is 1:3. The weight ratio of water to cement is 0.55, resulting in a total water content of 12% by weight in the mortar. 0.1g of defoamer is added.
[0173] As shown in Table 3, a certain amount of water-reducing agent (the polymer of this invention or the comparative agent listed in Table 3) was added to each mortar formulation. The density of each mortar was measured according to the test method, and the results are shown in Table 3. The slump of each mortar formulation was measured according to the test method, both immediately after preparation and after standing for 30 minutes. For the control (Control 1), no water-reducing agent was added to the mortar formulation. For the second control (Control 2), a commercial polycarboxylate ether water-reducing agent (PCENEX 111) was added to the mortar formulation. The results are shown in Table 3.
[0174]
Claims
1. An aqueous dispersion comprising polymer particles suspended in an aqueous medium, wherein the polymer particles comprise a polycarboxylic acid ether ("PCE") copolymer, the polycarboxylic acid ether copolymer comprising repeating units derived from: (a) 10 to 60 percent by weight of (meth)acrylic acid monomers; (b) 30 to 70 percent by weight of alkyl (meth)acrylate monomers; and (c) 5% to 40% by weight of polyethylene glycol ("PEG") monomers, each of which independently contains: (i) the (meth)acrylate moiety, which is linked to (ii) via an ester bond. (ii) Polyethylene glycol moieties containing an average of more than one ethylene oxide unit, and (iii) A terminal portion of the polyethylene glycol portion is attached to the end opposite the (meth)acrylate portion, the terminal portion being selected from hydrogen or alkyl portions; and (d) Other comonomers from 0 to 20% by weight Wherein (i) the weight percentage is based on the total weight of the PCE copolymer, (ii) the PCE copolymer has a comb-like structure comprising an acidic polymer backbone connected to a plurality of dangling polyethylene glycol side chains; and (iii) the weight-average molecular weight (M) of the polycarboxylic acid polymer ("HPP") produced when the ester bonds in the PCE copolymer are completely hydrolyzed. w The value is at most 100 kg / mol.
2. The aqueous dispersion of claim 1, wherein the PCE copolymer contains 25 to 45 wt% repeating units derived from (meth)acrylic acid monomers.
3. The aqueous dispersion of claim 1, wherein the PCE copolymer contains 34 to 55 percent by weight of repeating units derived from alkyl (meth)acrylate monomers, wherein the alkyl portion of the repeating units derived from the alkyl (meth)acrylate monomers contains an average of 1 to 3 carbon atoms.
4. The aqueous dispersion of claim 1, wherein the PCE copolymer contains 10 to 38 wt% repeating units derived from PEG monomers.
5. The aqueous dispersion of claim 4, wherein the repeating units derived from the PEG monomer in the PCE copolymer comprise an average of 4 to 15 ethylene glycol repeating units, and each terminal portion comprises an average of fewer than 8 carbon atoms.
6. The aqueous dispersion of claim 4, wherein the repeating units derived from the PEG monomer in the PCE copolymer comprise an average of at least 15 ethylene glycol repeating units, and each terminal portion comprises an average of at least 8 carbon atoms.
7. The aqueous dispersion according to claim 1, wherein the PCE copolymer is a random copolymer.
8. The aqueous dispersion according to claim 1, wherein the PCE copolymer is represented by formula 2: in: (a) Each R is independently an alkyl group containing an average of 1 to 3.5 carbon atoms; (b) Each R 1 Independently a hydrogen or alkyl group, wherein the alkyl group is selected such that R 1 On average, it contains fewer than 2 carbon atoms; (c) Each R 2 Independently a hydrogen or alkyl group; (d)-(CHR 3 -CH2O) n - is the polyethylene glycol portion as previously described, the polyethylene glycol portion comprising n repeating epoxy alkyl units; (e) Each R 3 Independently, it is hydrogen or a lower alkyl group; (f) Each M is independently a hydroxyl moiety, amide moiety, alkylamide moiety, nitrile moiety, halide moiety, acetate moiety, organic sulfonate moiety, or organic phosphate moiety; (g)x represents the number of repeating units derived from (meth)acrylic acid monomers; (h)y represents the number of repeating units derived from (meth)acrylate alkyl ester monomers; (i)z represents the number of repeating units derived from the PEG monomer; (j)m represents the number of repeating units derived from other comonomers; and (k) The end groups on the polymer backbone are not shown.
9. The aqueous dispersion according to claim 8, wherein in formula 2: (a) Each R contains an average of 1.5 to 2.5 carbon atoms; (b) Each R 1 On average, it contains at most 1.2 carbon atoms; (c) Each R 3 It contains an average of 0.0 to 0.2 carbon atoms; (d)x corresponds to repeating units derived from (meth)acrylic acid monomers at a weight percentage of 25 to 45%. (e)y corresponds to repeating units derived from (meth)acrylate monomers at a weight percentage of 34 to 55%; (f)z corresponds to repeating units derived from PEG monomers ranging from 10 to 38 wt%. (g)m corresponds to repeating units derived from other comonomers from 0 to 2 wt%; (h)(1) n averages 4 to 15, and R 2 Contains 0 to less than 8 carbon atoms, or (2) n averages at least 15, and R 2 It contains at least 8 carbon atoms; and (i) The repeating units are randomly distributed.
10. The aqueous dispersion according to any one of claims 1 to 9, wherein the weight-average molecular weight (M) of the HPP in the PCE copolymer is... w The concentration ranges from 12 kg / mol to 70 kg / mol.
11. The aqueous dispersion of claim 10, wherein the dispersion contains PCE copolymer particles with a Z-average particle size of 50 nm to 500 nm, and the aqueous dispersion contains 15 to 50% by weight of PCE copolymer based on the total weight of the aqueous dispersion.
12. The aqueous dispersion of claim 10, wherein the pH of the dispersion is from 2 to 6.
13. A method for preparing the aqueous dispersion according to claim 1, the method comprising the following steps: In an aqueous medium containing an emulsified surfactant and a polymerization initiator, under conditions suitable for producing PCE copolymers, the following substances are subjected to emulsion polymerization: (a) 10% to 60% by weight of (meth)acrylic acid monomer; (b) 30% to 70% by weight of alkyl (meth)acrylate monomers, wherein the alkyl moiety contains an average of 1 to 3.5 carbon atoms; and (c) 5% to 40% by weight of PEG monomers, each of which independently contains: (i) the (meth)acrylate moiety, which is linked to (ii) via an ester bond. (ii) A polyethylene glycol portion containing an average of more than one ethylene oxide unit; and (iii) A terminal portion of the polyethylene glycol portion is attached to the end opposite the (meth)acrylate portion, the terminal portion being selected from hydrogen or alkyl portions; and (d) 0% to 20% by weight of other comonomers The PCE copolymer has a comb-like structure comprising an acidic polymer backbone connected to a plurality of pendant polyethylene glycol side chains, wherein the weight-average molecular weight (M) of the polycarboxylic acid polymer (HPP) produced when the ester bonds in the PCE copolymer are completely hydrolyzed is... w The weight percentage is up to 100 kg / mol, where the weight percentage is based on the total weight of the monomer.
14. A cementitious mixture comprising dry components (i) to (iii): (i) Packing material; (ii) Cement; (iii) At least 0.05% by weight of the PCE copolymer or its hydrolysis product, based on the weight of the cement. Optionally, it also contains water, wherein the PCE copolymer comprises repeating units derived from: (a) 10 to 60 percent by weight of (meth)acrylic acid monomers; (b) 30 to 70 percent by weight of alkyl (meth)acrylate monomers; and (c) 5% to 40% by weight of polyethylene glycol ("PEG") monomers, each of which independently contains: (i) the (meth)acrylate moiety, which is linked to (ii) via an ester bond. (ii) Polyethylene glycol moieties containing an average of more than one ethylene oxide unit, and (iii) A terminal portion of the polyethylene glycol portion is attached to the end opposite the (meth)acrylate portion, the terminal portion being selected from hydrogen or alkyl portions; and (d) Other comonomers from 0 to 20% by weight Wherein (i) the weight percentages in (a), (b) and (c) are based on the total weight of the PCE copolymer, (ii) the PCE copolymer has a comb-like structure comprising an acidic polymer backbone connected to a plurality of pendant polyethylene glycol side chains; and (iii) the weight-average molecular weight (M) of the polycarboxylic acid polymer ("HPP") produced when the ester bonds in the PCE copolymer are completely hydrolyzed. w The value is at most 100 kg / mol.
15. A polycarboxylate ether (PCE) copolymer, said polycarboxylate ether copolymer comprising repeating units derived from: (a) 10 to 60 wt% (wt%) of (meth)acrylic acid monomers; (b) 30% to 70% by weight of alkyl (meth)acrylate monomers, wherein the alkyl moiety contains an average of 1 to 3.5 carbon atoms; and (c) 5% to 40% by weight of PEG monomers, each of which independently contains: (i) the (meth)acrylate moiety, which is linked to (ii) via an ester bond. (ii) A polyethylene glycol moiety containing, on average, more than one ethylene oxide unit; and (iii) A terminal portion of the polyethylene glycol portion is attached to the end opposite the (meth)acrylate portion, the terminal portion being selected from hydrogen or alkyl portions; and (d) 0% to 20% by weight of other comonomers Wherein (i) the weight percentage is based on the total weight of the PCE copolymer, (ii) the PCE copolymer has a comb-like structure comprising an acidic polymer backbone connected to a plurality of dangling polyethylene glycol side chains; and (iii) the weight-average molecular weight (M) of the polycarboxylic acid polymer ("HPP") produced when the ester bonds in the PCE copolymer are completely hydrolyzed. w The value is at most 100 kg / mol.
Citation Information
Patent Citations
Redispersible powder composition for dry mortar formulations
US9181131B2